If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = -5x + 7 Reorder the terms: 17 = 7 + -5x Solving 17 = 7 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 17 + 5x = 7 + -5x + 5x Combine like terms: -5x + 5x = 0 17 + 5x = 7 + 0 17 + 5x = 7 Add '-17' to each side of the equation. 17 + -17 + 5x = 7 + -17 Combine like terms: 17 + -17 = 0 0 + 5x = 7 + -17 5x = 7 + -17 Combine like terms: 7 + -17 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| 3-11=13 | | 1/8-3/8 | | (f+9)(f+7)=0 | | -10x-5=5 | | 25-x-13=5 | | 2d^3-13d-7=0 | | 74-x-5=50 | | x^2-(3-k)x+2-2k=0 | | 8e=-24 | | 5x(x+1)-3(x-2)=17 | | x^2-10x+14= | | 3+2=17 | | 0=60-1/2(9.8)t^2 | | 90-x-23=59 | | -x-sqrt(40-7*x^2)1/2 | | 60-x-4=25 | | 7(5n-1)+3= | | -x-sqrt(40-7x^2)1/2 | | T/5=10/3 | | 60-1/2(9.8)x^2=0 | | -a-sqrt(40-7a^2)1/2 | | 0.5x=18-x | | 2x^2+128-32x=0 | | 20-x-3=15 | | 9x+4-x=4(2x+1) | | 0.21(84)= | | 10x^3+35=0 | | X+8-5X+4=0 | | 6z+7z=14 | | (2x^2-3x+1)(2x^2+5x-1)=9x^2 | | x-52+x=180 | | 4b^2+10=-10 |